W8 Surviving and thriving training: teaching wellbeing and resilience through simulation. (5th November 2017) - Nash, Eleanor; Sathanandan, S; Pimblett, M
Abstract : Background and Aims: The importance of the health and wellbeing of the medical workforce is increasingly being recognised. Rising numbers of doctors-in-training are suffering burnout and stress from demands in the workplace (1). The health of the workforce has been shown to directly impact patient care (2). We have created videos of simulated scenarios depicting doctors' stresses in the workplace, with the scenarios demonstrating how stress manifests in individuals in the clinical environment. Watching the scenarios and the subsequent debrief, will increase awareness of signs of not coping in colleagues (and oneself), and encourage conversations on stress and burnout, how to manage it and the support available for doctors. Session Description: Part 1: A mini workshop of a "surviving and thriving" training session Initial introduction to the topic Two of the videos will be shown (each lasts approximately five minutes). After each video, in small groups, discuss the scenario, the signs of stress in the doctor and how the doctor reacted in the situation. A subsequent whole group discussion will be lead by workshop facilitator, on signs of stress and not coping in colleagues, and how they are displayed in the workplace. Participants will be encouraged to reflect upon ways of identifying stress in colleagues and oneself and possible coping methods. The workshop includes providing a resource on additional support services. Part 2: Designing and delivering a "surviving and thriving" training session Stress and burnout remains stigmatised and under-recognised, therefore can be a difficult and sensitive topic to teach. Our experiences in overcoming these obstacles to create a successful and sustainable teaching resource can be shared to help others interested in developing similar programmes. The videos are a free teaching resource available for use. In this section we provide advice on how to use the videos as a teaching resource, and tips for those planning on developing their own workshops on the topic. Learning Objectives: Highlight the importance of doctors' health and wellbeing Experience a "surviving and thriving" teaching session How to create a similar teaching programme Signs of stress in the workplace and support services that are available. Target Audience: Human Patient Training Facilitators Medical educators Junior doctors Maximum number of participants: 30: